La aplicación física de la geometría astral como confirmación de la teoría kantiana del conocimiento - Cano de Pablo, Juan (Logos. Anales del Seminario de Metafísica, 2007)
The appearance of the non-Euclidean or astral geometries seemed to contradict the philosophy of the Kant´s mathematics. He had considered the possibility of a supreme geometry, but he discarded it due to it was not synthetically related with the experience. However, at the beginning of the XX century Albert Einstein developed the Theory of the Relativity and made it a theory of gravitation. This theory, known as Theory of the General Relativity, confers to the Universe a non Euclidean structure. In this article it is outlined that such an endowment of physical sense to an astral (spherical Geometry or Riemanniana) geometry kind, makes that the mistrust that Kant manifested with respect to a possible geometry different to that which the intuition presents to us, will vanish. The Theory of Relativity so recovers the necessary connection between the new geometry and the experience.